MO1015: Ferric Carboxymaltose and SARS-COV-2 Vaccination-Induced Immunogenicity in Kidney Transplant Recipients with Iron Deficiency: The Covac-Effect Randomised, Placebo-Controlled Clinical Trial. (3rd May 2022) - Sophia Jacoline Vinke, Joanna; Altulea, Dania; Freerk Eisenga, Michele; Jagersma, Renate; Niekolaas, Tessa; van Baarle, Debbie; van der Heiden, Marieke; Steenhuis, Maurice; Rispens, Theo; Abdulahad, Wayel; Sanders, Jan-Stephan; De Borst, Martin
Abstract: BACKGROUND AND AIMS: Kidney transplant recipients (KTRs) have a compromised immune response after vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Iron deficiency (ID) impairs B cell proliferation and function, may reduce vaccine efficacy and is highly prevalent among KTRs. We aimed to investigate whether ID correction by ferric carboxymaltose (FCM) treatment improves humoral and cellular responses after SARS-CoV-2 vaccination in iron-deficient KTRs. METHOD: In this analysis of an ongoing randomised, double-blind, placebo-controlled clinical trial, iron-deficient KTRs [serum ferritin < 100 μg/L or serum ferritin 100–300 μg/L in combination with transferrin saturation (TSAT) <20%] received up to four doses of 500 mg intravenous FCM or placebo at 6-week intervals (Fig. 1). In the primary intention-to-treat analysis, we determined the effect of ID correction on anti-SARS-CoV-2 IgG titers (ELISA) and T-lymphocyte reactivity against SARS-CoV-2 (ELISPOT) following SARS-CoV-2 vaccination with mRNA-1273 ( N = 41) or mRNA-BNT162b2 ( N = 5). RESULTS: Out of the 46 trial participants (median age 53 (interquartile range 43–65) years, 61% male), 25 were assigned to receive FCM and 21 to receive placebo. FCM treatment efficiently restored iron status: serum ferritin levels increased from 49 (26–79) μg/L at baseline to 464 (272–621) μg/L at 4 weeks after the second vaccination ( P < .001 versus baseline; P < .001 versus placebo group) and TSAT from 21% ± 8% to 34% ± 12% ( P < .001 versus baseline; P <.001 versus placebo group), while ID persisted in the placebo group. At 4 weeks after the second vaccination, anti-SARS-CoV-2 IgG titers tended to be lower in the FCM arm [66.51 (12.02–517.59) BAU/mL; placebo arm: 115.97 (68.86–974.67) BAU/mL, P = .07, Fig. 2A]. SARS-CoV-2 specific T-lymphocyte activation did not differ between the study arms [FCM arm: 93.3 (0.85–342.5) IFN-ɣ spots per 10 6 PBMCs, placebo arm: 138.3 (0.0–391.7) IFN-ɣ spots per 10 6 PBMCs, P = .83, Fig. 2B]. Anti-SARS-CoV-2 IgG titers and T-lymphocyte reactivity against SARS-CoV-2 significantly correlated with each other (Spearman's rho 0.44, P = .002), but not with ferritin levels at 4 weeks after the second vaccination (ferritin versus anti-SARS-CoV-2 IgG titer, Spearman's rho –0.15, P = .33; ferritin versus T-lymphocyte reactivity against SARS-CoV-2, Spearman's rho –0.01, P = .98). Results were similar in a per-protocol analysis and in sensitivity analyses after the exclusion of individuals with low total IgG levels or mild ID at baseline or patients who received alemtuzumab, anti-thymocyte globulin or high-dose methylprednisolone during the previous 2 years. Separate analyses in subgroups according to immunosuppressive regimen (dual or triple therapy) or vaccine type also yielded highly similar results. CONCLUSION: FCM treatment efficiently restored iron status in KTRs but did not improve the humoral or cellular immune response against SARS-CoV-2 after two vaccinations. (Funded by Dutch Kidney Foundation, Vifor Fresenius Medical Care Renal Pharma and the Tekke Huizenga Foundation (grant no STHF 2021.01.02); COVAC-EFFECT/EFFECT-KTx ClinicalTrials.gov number, NCT03769441.)